THE VALUE AND MEANING OF MOANGGO IN TOLAKI SOCIETY IN SOUTH EAST SULAWESI - Idaman Idaman; Sitti Aminah (Universitas Islam Negeri Alauddin Makassar, 2017)
Moanggo, an oral literature of Tolaki people is currently at risk of being wiped out as it is now only rarely played at traditional wedding ceremonies in Tolaki. It is among the identity markers of Tolaki people loaded with messages for private, family and social lives. On this basis, this study aims to (1) Describe the meaning contained in Moanggo as a local literature of Tolaki people. (2) Describe the values contained in Moanggo as a traditional oral literature of Tolaki people.This research is a qualitative descriptive study. To achieve the objectives, this study applies the theoretical framework of Paul Ricœur’s hermeneutics. Data sources to be examined in this investigation comprise some informants and the Anggo text itself. The data are also obtained from observations, interviews and documents. The data are then analyzed using Milles and Huberman’s technical data analysis, namely: 1) Data collection, 2) Data reduction or simplification of data, 3) Presentation of data, and 4) inference / verification.The results indicate that the meaning of the Anggo text in oral narrative of Moanggo cannot be separated from the socio-historical cultural context when it is narrated. Therefore, every text has been linked with the socio-cultural context of Tolaki people at present time, and it is of course a representation of the history of life of Tolaki people in the past. The values contained in the Anggo text comprise the value of education, moral values, cultural values and philosophical values. Moanggo as an oral literature of Tolaki people is an identity marker for Tolaki people, and it is presently at risk of extinction due to its lack of use in wedding customs and other cultural activities. Therefore, the preservation of the oral literature Moanggo needs to be maintained by both the government and the Tolaki society.